2020
DOI: 10.1016/j.cej.2019.123114
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of diffusion coefficients for multiple penetrant/polyolefin systems based on sorption data

Abstract: The binary and ternary diffusion coefficients for gas/polymer systems can be estimated from solubility data and an equation of state to the free volume of penetrant/polymer systems. The system free volume can be calculated by the Sanchez Lacombe equation-of-state (SL-EoS), eliminating the need for viscoelastic data in determination of free volume parameters. Furthermore, this approach accounts for polymer swelling. The model gives reliable predictions for both binary and ternary systems of alkanes and alkenes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…The 𝜉 i3 parameter is the ratio of polymer and solvent molar jumping units, [40] defined as follows: [32,38]…”
Section: Vrentas and Duda Diffusion Modelmentioning
confidence: 99%
“…The 𝜉 i3 parameter is the ratio of polymer and solvent molar jumping units, [40] defined as follows: [32,38]…”
Section: Vrentas and Duda Diffusion Modelmentioning
confidence: 99%
“…However, if one knows the diffusivity in question, then the sorption experiments can be used to solve the inverse problem using the sorption curves to estimate the parameters of the substructural size distribution. In this case we used the model and parameters of Alves et al [7] to calculated the diffusivity of ethylene in LLDPE. Their diffusivity values of ethylene in LLDPE should be comparable to those of the LLDPE powders used here as the they used a polymer with a crystallinity of 48.6% for Alves et al [1] The values used in the present work are shown in Table 1.…”
Section: Estimation Of Distribution Parametersmentioning
confidence: 99%
“…The experimental sorbed weight were therefore fitted to Crank's diffusion equation to estimate the average size of Table 1. Diffusivity data were taken from Alves et al [7] at 70 °C. particles, r m , and the standard deviation, 𝜎, in Equation ( 3).…”
Section: Estimation Of Distribution Parametersmentioning
confidence: 99%
See 2 more Smart Citations